A qualitative assessment of the business continuity practices of selected ASEAN banks in response to the COVID-19 pandemic - Carbonel, Hillary Anne V. (Animo Repository, 2022)
Many economies rely heavily on the banking sector for their productivity and development, so much so, that any disruption could result in the stagnation of business and organizational operations worldwide. Due to this, central banks encourage the use of business continuity practices to exercise conservatism in assessing all the risks involved in their external and internal environment. This study aims to qualitatively assess the business continuity practices enacted by the 20 selected ASEAN banks before and during the COVID-19 pandemic. To assess these practices, the researchers adopted and modified frameworks from each central bank to come up with a collective framework, which was then reviewed by three assessors. After the assessment, the strategies were collected to create an inventory of actions for future banks to follow. There are two research propositions in this study: (1) the practices for pandemic-related risks that the Banks disclosed in 2018 and 2019 align with the practices implemented during the years 2020 to 2021; and (2) that the selected ASEAN banks have adhered to the criteria of the collective framework on the assessment of a bank’s preparedness in the event of a pandemic, both in their implementations and disclosures. The results of the study uphold the first proposition as Banks were continually implementing the practices they had disclosed against the COVID-19 pandemic. This includes the integration of early warning systems and the investment in the development of disaster recovery centers. However, there were certain additions to their practices during the outbreak, which included specific mentions of pandemic and high-absenteeism risks. Moreover, the Banks also tightened their systems and restructuring programs, enacting a more conservative approach to default and credit risks. However, the results of the study only partially uphold the second proposition as the Banks were not able to adhere to certain criteria in the collective framework. This includes the inclusion of pandemic and high-absenteeism risks before the outbreak, elaboration of table-top exercises, disclosure of recovery time objectives, recovery point objectives, and operational breakdowns. The researchers point out their reasons for exclusion on the lack of emphasis by their respective central banks or confidentiality purposes. Despite this, the researchers found that the banks had proven to be resilient against the COVID-19 Pandemic by being able to respond to the outbreak with their continuous assistance to employees, the performance of stress tests, and further investment in disaster recovery centers. Just the same, the researchers recommend that the Board of Directors review their identified excluded practices for inclusions in its future disclosures. Moreover, the central banks could make use of the collective framework in updating the standardized framework they periodically release. It is also recommended that future banks make use of the created inventory of practices to respond more proactively to similar disruptions. Keywords: business continuity practices, pandemic risk, banking sector, ASEAN